Dielectric properties of calcium doped BaTi0.85Sn 0.15O3: A diffuse phase transition - Singh S.; Singh P.; Parkash O.; Kumar D. (My University, 2025)
Effect of calcium substitution on dielectric behavior of BaTi 0.85Sn0.15O3 was studied over 1-106 Hz and 120-370 K. Compositions with x=0.00, 0.14, 0.16 and 0.20 in the system (Ba 1-xCax)(Ti0.85Sn0.15)O3 were prepared by solid state reaction route. Compositions with x=0.00,0.14 and 0.16 are found to be cubic single phase at room temperature which is confirmed by their X-ray diffraction studies. However, the sample with x=0.20 shows lines of constituent oxides. The SEM micrographs of the investigated systems show the existence of ferroelectric domains at room temperature. The temperature dependence of ′ of this system exhibits a broad maxima near room temperature. Diffuseness of phase transition increases with increasing calcium substitution. A dielectric relaxation due to rattling of Ca ion is observed in x=0.14 and 0.16 at low temperatures. The diffuse phase transition (DPT) behavior observed in the investigated compositions is also confirmed by the hysteresis loop measurement. Moreover, hysteresis loop measurement shows that coercivity and remanent polarization both decrease with increasing Ca concentration. © 2010 Elsevier B.V. All rights reserved.